PENGARUH KOMPETENSI, INDEPENDENSI DAN PROFESIONALISME TERHADAP KUALITAS AUDIT (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK SE SUMATERA) - Restu Agusti; Nastia Putri Pertiwi (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2013)
The purpose of this research is to research the influence of competency level,auditor independency and profosionalism to the audit quality. Competency,independency and profosionalism are three characteristics that must be have bythe auditor.The population of this research is an external auditor. The sample that isresearched is auditor who works in public accounting that domiciled inSumatera.There are 163 questionnaires being spread. The returned questionnaireare 89. this research is used result test double regression linear, they are t testand F test.This research gives empirical research to support the competency influence,independency, profesionalism auditor to the audit quality partially andsimultaneously.Kata Kunci : Audit quality, competency, independency, profesionalism